Insultos, elogios e resistências: participação de repentistas negros em cantorias do Nordeste (1870-1930). - Gomes, Germana Guimarães (2012)
The research developed - linked to the search line History of the Regional Program of Graduate Studies in the Historyof the Federal University of Paraiba, with area of concentration in History and Historical Culture,has as its theme, the participation of repentistas blacks in singing northeast of the end of the century XIX and beginning of the century XX. This time adopted in points for the period in which blacks were faced with a backdrop provided by the abolition, which was associated with the new form of "integration", even though still excluding this segment in the early Republic. Using bursts that were corporated by Cordel Literature, as well as classics of the beginning of the century XX, they intend to discuss how repentistas blacks were represented by their opponents in singing in which they participated. Accordingly, we found the "insults" that put the repentista black in the context of inferiority, exclusion, "compliments," that mask the prejudices, but which shows positive visions of the Black opponent, since this, in the course of battle, exposes their knowledge, techniques, and finally, resistance, since the black Singer that highlighted in singing when positioned against certain representations, conferred by opponents "white" about their race and practices. Checking the continuity of these representations stereotyped and discriminatory in the present, this study will enable the understanding about the maintenance of the speeches, as well as a reflection on the position of black populations faced with the situations excludentes to them and (still) being checked.